ASAS NON DISKRIMINASI DALAM CONTEMPT OF COURT - Nur Kholis (Legality : Jurnal Ilmiah Hukum, 2018)
This research raises the title of non discrimination principle in contempt of Court with legal issue (1). Non-discrimination Principles as the basis for the application of Contempt of Court criminal acts and (2). Formulation of sanction of Contempt of Court crime by using method (1). Normative research type, (2). Approach problems that include (a). Conceptual approach, (b). Legal Approach, (c). Case approach and (d). Comparative approach. The result of this dissertation research in the form of Contempt of court is an insulting behavior, disobedient to the order of the court institution (harassment) which has been included in the criminal law realm. Contempt of court derived from common law system, not derived from countries that the legal system embraces Civil law system including the State of Indonesia. While in Indonesia first knew Contempt of Court on the enactment of Law No. 14 of 1985 on the Supreme Court of the Republic of Indonesia. The Criminal Code (KUHP) does not regulate the crime of Contempt of court, but only acts or criminal acts in the Criminal Code are categorized into the realm of criminal acts Contempt of court, so that the Judge (court) is only a legal object of action criminal Contempt of court. The Non-Discrimination Principle can be applied to the crime of Contempt of Court because all legal subjects must be equal before the law, so that the application of the principle of Non-Discrimination judges will be the subject of law, so there is a shift in the concept of being a legal subject because it is based on the principle of Non Discrimination. The norm as a Contempt of court arrangement is stated as "everyone ...".